Implementasi Moderasi Beragama pada Kurikulum Merdeka di Sekolah Dasar - Maratul Qiftiyah; Diah Rizki Nur Kalifah; Rara Rengganis (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This study aims to examine the implementation of religious moderation in the merdeka curriculum in Elementary Schools, focusing on SDN 1 Sumber Agung which has implemented this curriculum program. This study uses a descriptive qualitative approach, this study involves teachers, principals, and students as research subjects. Data collection was carried out through interviews, observations, and documentation studies. The study results indicate that religious moderation is integrated into thematic and project-based learning methods. Teachers play an important role in conveying moderation values ​​such as tolerance, balance, and respect for differences. Although this program has a positive impact on the formation of student character, there are challenges in the form of teachers' lack of understanding of the concept of religious moderation and resistance from some parents. This study recommends improving teacher training, socialization with parents, and developing extracurricular programs that support religious moderation. The results of this study provide new insights into implementing religious moderation values ​​in elementary education through the merdeka curriculum.